TINJAUAN YURIDIS PEMBEBANAN GANDA ATAS OBJEK JAMINAN DAN IMPLIKASINYA TERHADAP KEDUDUKAN KREDITUR - Tri Wani Andini; Rr. Savita Helena Affandy; Hendrajogi simanjuntak; Jerry Indrawan (Jurnal Yustitia, 2026)
In Indonesia, material collateral plays an important role so that creditors feel more secure in distributing financing by providing loans to debtors. One of the fundamental principles in collateral law is the principle of legal certainty, where each collateral object can ideally only be encumbered by one type of binding to guarantee one or several particular debts. However, in practice, the phenomenon of double pledging still often occurs and gives rise to various legal issues. This condition creates the potential for conflicts of interest, especially regarding the priority of repayment to creditors if the debtor is in default. The purpose of this study is to analyze the legal certainty of double pledging and examine the legal protection for creditors of double pledging. This writing is conducted normatively with library research by collecting Primary legal materials such as applicable laws and regulations, Secondary legal materials such as books and journals, and Tertiary legal materials such as articles on the internet. The conclusion is that legal certainty for double pledging is essentially guaranteed in positive law through the principle of publicity (registration of collateral), the principle of priority based on the registration date, the executorial power of the collateral certificate, and explicit provisions in the mortgage law and the fiduciary law regarding the creditor's position. With this mechanism, even though double pledging still occurs in practice, legal protection for the first creditor remains strong, so that the structure of legal certainty is maintained.